Psychological risk in long‐term survivors of childhood acute lymphoblastic leukemia and its association with functional health status: A PETALE cohort study. Issue 11 (7th August 2018) - Anestin, Annélie S.; Lippé, Sarah; Robaey, Philippe; Bertout, Laurence; Drouin, Simon; Krajinovic, Maja; Michon, Bruno; Rondeau, Émélie; Samoilenko, Mariia; Laverdière, Caroline; Sinnett, Daniel; Sultan, Serge
Abstract: Background: Recent research has suggested that long‐term pediatric cancer survivors were at risk of important physical and psychological morbidities. To date, we do not know to what extent functional health status contributes to psychological risk and which domains are most important. The aim of this study was to systematically explore which functional domain could explain anxiety, depression, and distress symptoms. Procedure: We used data available for 105 adolescents and 182 adults successfully treated for childhood acute lymphoblastic leukemia at two Canadian sites part of the PETALE cohort. Participants were ≥5 years postdiagnosis, aged 22 ± 6 years, 52% female, and 49% acute lymphoblastic leukemia high‐risk status. The contribution of health functional status (15D/16D questionnaires) to self‐reported anxiety, depression, and distress (Beck scales and distress thermometer) was evaluated using adjusted logistic regression models. Results: Prevalence rates found for mild–severe anxiety, depression, and distress were 14%, 21%, and 30% among adolescents and 27%, 20%, and 19% among adults. Frequent health domains associated with psychological risk were sleeping and breathing in adolescents, and vitality/fatigue, discomfort/symptoms, mental function, and sleeping in adults. Mental function was systematically associated with psychological risk across age groups (median OR = 10.00, 95% CI 3.01–33.71). Exploratory mediation bootstrapping analyses suggested that the effect on psychological risk of overall health status and mental function problems was partly explained by social/work/school functioning. Conclusion: The results identified important functional health domains that could be targeted for interventions preventing psychological risk: vitality/fatigue, discomfort/symptoms, sleeping, and mental function issues. Health domains probably affect mood partly by limiting social/work/school functioning.